2016
DOI: 10.4040/jkan.2016.46.5.697
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model of Evidence-Based Practice Implementation among Clinical Nurses

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution NoDerivs License. (http://creativecommons.org/licenses/by-nd/4.0) If the original work is properly cited and retained without any modification or reproduction, it can be used and re-distributed in any format and medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…Barriers to conducting EBP for Korean nurses include: the lack of knowledge and skills, lack of belief and capacity, lack of database access and utilization, and insufficient critical thinking and motivation [2022]. The barriers to conducting EBP in Korea at the organizational level are organizational culture, insufficient education programs, lack of well-trained EBP experts, lack of time, and inadequate communication [20, 21, 23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers to conducting EBP for Korean nurses include: the lack of knowledge and skills, lack of belief and capacity, lack of database access and utilization, and insufficient critical thinking and motivation [2022]. The barriers to conducting EBP in Korea at the organizational level are organizational culture, insufficient education programs, lack of well-trained EBP experts, lack of time, and inadequate communication [20, 21, 23].…”
Section: Introductionmentioning
confidence: 99%
“…First, EBP implementation is influenced by the knowledge, skills, and beliefs of the individual nurse on EBP [22, 25, 26]. At the organizational level, it is necessary to create an organizational culture that strengthens and supports the nurse’s values and beliefs on EBP, and to share the common beliefs or values of its members to achieve the common goal of successful implementation of EBP [12, 27].…”
Section: Introductionmentioning
confidence: 99%
“…All items employed in examples of assistance through the creation of EBP groups. The research conducted in Korea, contrary to research, organizations, learners, and organizations related to statistics do not correlate with the implementation of EBP (Park and Jang, 2016) and more on beliefs and knowledge at the individual level that has the optimum role. In another Korean study stated that the combination of organizational DOI: 10.30994/sjik.v9i2.338 ISSN: 2252-3847 (print); 2614-350X (online) Vol.9 No.2 November 2020 Page.1504-1511…”
Section: Implementation Of Ebp Nurses On An Individual Levelmentioning
confidence: 59%
“…Two different studies conducted in South Korea (Park and Jang, 2016;Yoo et al, 2019) showed that there positively increased in EBP on the knowledge/ skills of EBP of Korean nurses. In contrast to research conducted in Greece (Patelarou et al, 2016) reported that half of the nurses said they were not sure of their ability to be involved in EBP.…”
Section: Implementation Of Ebp Nurses On An Individual Levelmentioning
confidence: 99%
“…국내 연구로는 임상간호 근거기반실무 준비도에 영향을 미 치는 요인 [9], 촉진요인 [18], 근거기반실무 실행 구조모형 [19] 정보검색 및 연구 활용능력 [20], 간호조직의 근거기반실무 활 성화 프로그램 개발 [5]에 대한 연구가 있었다. 또한 국내 간호 사들이 실무현장에서 근거기반실무를 적용하는 경우는 20% 로 나타나 [20], 근거기반실무 필요성에 비해 활성화 정도는 낮 은 실정이었다 [9,20,21].…”
unclassified